RSV Pseudovirus Neutralization Assay v1 - Cassandra A. L. Simonich; Teagan E. McMahon; Xiaohui Ju; Timothy C. Yu; Natalie Brunette; Terry Stevens-Ayers; Michael J. Boeckh; Neil P. King; Alexander L. Greninger; Jesse Bloom (2025)
Here, we develop an experimental system for measuring neutralization titers against RSV F using pseudotyped lentiviral particles. This system is easily adaptable to evaluate neutralization of relevant strains. This method is first described in the manuscript: SimonichCAL,McMahonTE,JuX,YuTC,BrunetteN,Stevens-AyersT,BoeckhMJ,KingNP,GreningerAL,BloomJD.2025.RSV F evolution escapes some monoclonal antibodies but does not strongly erode neutralization by human polyclonal sera. J Virol99:e00531-25. https://doi.org/10.1128/jvi.00531-25